Integrating Western Management Theories with Indigenous Knowledge Systems: Ethical Conduct and Development in the Indian Subcontinent’s Informal Sector. - Mamta Hegde (European Economic Letters (EEL), 2024)
This study explores integrating Western management theories with indigenous practices in the Indian subcontinent, focusing on enhancing ethical conduct and management practices within the informal sector. Through a comprehensive analysis of case studies from India, Pakistan, Bangladesh, and Sri Lanka, the research highlights the importance of culturally adapted management strategies that blend Western theories' structured frameworks with local practices' cultural relevance. Key findings reveal that such integration promotes higher ethical standards, operational efficiency, and sustainable development. The study offers practical recommendations for policymakers, managers, and practitioners to foster inclusive and effective management practices, emphasizing the significance of community involvement and frugal innovation. Future research directions include sector-specific studies, comparative regional analyses, and the impact of digital transformation on hybrid management models.